DISTRIBUTION OF WOOD DENSITY IN A SINGLE STEM OF POPULUS EURAMERICAN A (Biological Sciences - PJSIR, 2022)
Four 12-years old trees of Populus euramericana harvested in Faisalabad and Toba Tek Singh Districts wereanalysed to determine the density distribution in the stem. Density increased with age and increasing height. Minimumdensity noted was 0.25 g/cm" and maximum density was 0.56g/cm3.